Friendship adventures : DreamWorks Storytellers Collection (DreamWorks storytellers collection., 2014)
Retells stories based on such popular Dreamworks animated films as "Shrek," "Madagascar," "How to Train Your Dragon," and "Kung Fu Panda" that focus on the role of the friendships among the characters in their adventures.